Thiol/disulfide homeostasis in untreated schizophrenia patients. (May 2017) - Topcuoglu, Canan; Bakirhan, Abdurrahim; Yilmaz, Fatma Meric; Neselioglu, Salim; Erel, Ozcan; Sahiner, Safak Yalcin
Abstract: Backround: The aim of the study was to investigate dynamic thiol/disulfide (SH/SS) homeostasis in untreated schizophrenia. Methods: Blood thiol/disulfide homeostasis status, which reflects native thiol-disulfide exchanges, was investigated in 87 untreated patients (52 males, 35 females), and the obtained results were compared with 86 healthy controls. Blood serum native thiol and total thiol (ToSH) concentrations were measured in a paired test. The half value of the difference between native thiol and ToSH concentrations was calculated as the disulfide bond amount. Results: SH and ToSH concentrations were found to be significantly lower (p<0.001 for both) in patients with untreated schizophrenia compared with the control group, whereas disulfide levels were significantly higher (p<0.001). Schizophrenia patients had significantly higher SS/ToSH and SS/SH ratios and a significantly lower SH/ToSH ratio compared to those of healthy individuals. Conclusions: SH and ToSH amounts were found to be insufficient in untreated schizophrenia patients. Additionally, according to the results of the study, thiol/disulfide homeostasis was also disturbed by a shift to the disulfide bond formation side. This might affect the neurotransmission processes, which are known to be related with many symptoms observed in schizophrenia. The replacement of the thiol gap and the reduction of excess SS amounts might have a positive effect in supporting therapy for schizophrenia patients. Highlights: We evaluated thiol/disulfide homeostasis in untreated patients with schizophrenia. Native thiol and total thiol concentrations were found lower in patients with schizophrenia than the control group. Disulphide levels were higher in patients with schizophrenia compared to the control group.